An uncommon variant of rare type of muscular dystrophy - A., Jayashankar C.; Somasekar, D. S.; Gurucharan, Adoor; Perugu, Pavan Kumar; V., Ashwath S.; Santosh, K.V. (International Journal of Research in Medical Sciences, 2017)
The muscular dystrophies are a group of hereditary degenerative diseases characterised by progressive myopathy. Emery-Dreifuss muscular dystrophy (EDMD) is a rare genetically heterogenous type of muscular dystrophy characterized by early contractures (especially in the neck, elbows and ankles), slowly progressing muscle weakness more prominent in humeroperoneal region, onset in early childhood and cardiac problems. Emery-Dreifuss muscular dystrophy is commonly inherited in an X linked recessive pattern and rarely autosomal dominant inheritance or autosomal recessive fashion. Here we report a case of autosomal recessive type of Emery-Dreifuss muscular dystrophy from our hospital.